A Decade of Iontronic Delivery Devices. Issue 5 (12th March 2018) - Arbring Sjöström, Theresia; Berggren, Magnus; Gabrielsson, Erik O.; Janson, Per; Poxson, David J.; Seitanidou, Maria; Simon, Daniel T.
Abstract: In contrast to electronic systems, biology rarely uses electrons as the signal to regulate functions, but rather ions and molecules of varying size. Due to the unique combination of both electronic and ionic/molecular conductivity in conjugated polymers and polyelectrolytes, these materials have emerged as an excellent tool for translating signals between these two realms, hence the field of organic bioelectronics. Since organic bioelectronics relies on the electron‐mediated transport and compensation of ions (or the ion‐mediated transport and compensation of electrons), a great deal of effort has been devoted to the development of so‐called "iontronic" components to effect precise substance delivery/transport, that is, components where ions are the dominant charge carrier and where ionic–electronic coupling defines device functionality. This effort has resulted in a range of technologies including ionic resistors, diodes, transistors, and basic logic circuits for the precisely controlled transport and delivery of biologically active chemicals. This Research News article presents a brief overview of some of these "ion pumping" technologies, how they have evolved over the last decade, and a discussion of applications in vitro, in vivo, and in plantae. Abstract : Iontronic delivery devices comprise components and circuits where ions are the dominant charge carriers and where ionic–electronic coupling defines device functionality. This article presents a brief overview of some iontronic technologies, how they have evolved over the last decade, and a discussion of applications in vitro, in vivo, and in plantae.